Anti-friction coating with transverse gradient and preparation method thereof

Through the in-situ molding technology of the electric jet mask, the friction reduction coating with a lateral gradient is formed on the friction surface, which solves the problem of insufficient flatness and binding force of the traditional coating under lateral shear stress, and achieves better lubricating performance and anti-peel properties extend service life.

CN119465143AActive Publication Date: 2025-02-18SHANDONG UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411522326.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-18
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

When traditional gradient friction reducing coatings face lateral shear stress, it is difficult for the coating surface to remain flat, resulting in limited friction reducing performance. Under high stress or high temperature conditions, the bonding force between layers is insufficient, resulting in The coating peels off or cracks, losing its friction reduction function.

Method used

The in-situ molding technology of the electric jet mask is used to realize the composition gradient changes of the self-lubricating material powder and metal powder along the direction parallel to the friction surface, forming a uniform and dense lateral gradient friction reduction coating.

Benefits of technology

Through the lateral gradient structure, stress is evenly distributed, local stress concentration is reduced, the lubricating performance of the coating is improved, the anti-peel and cracking properties are anti-splitting and cracking properties are extended, and the service life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465143A_ABST
    Figure CN119465143A_ABST
Patent Text Reader

Abstract

The invention discloses an antifriction coating with transverse gradient and a preparation method thereof, and belongs to the technical field of antifriction coatings. The coating comprises self-lubricating material powder and metal powder which are combined into a whole; the ratio of the self-lubricating material powder to the metal powder is changed in a gradient manner along the direction parallel to the friction surface; the self-lubricating material powder is selected from one or more of MoS2 and WS2; the metal powder is selected from one of Ti, Co or Ni; the mass ratio of the self-lubricating material powder to the metal powder is (5-10): (0-5). Due to the fact that the material property is gradually changed in the friction force direction, stress is more evenly distributed on the surface of the coating and is not limited to the interface in the vertical direction any more, and local stress concentration can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-friction coatings, and in particular to an anti-friction coating with a lateral gradient and a preparation method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Anti-friction coating is a coating provided on the surface of the friction component to reduce the friction coefficient of the friction pair, including gradient anti-friction coatings with gradient changes in composition and performance. The traditional gradient anti-friction coating structure includes multiple layers parallel to the friction surface, and the composition and performance of each layer show a gradient change perpendicular to the friction surface. There is an obvious interlayer interface between the layers, and the gradient fusion of the material composition is achieved in the process of layer-by-layer wear from the surface to the inside of the coating during service. Although the interfacial stress on the layer interface can be reduced to a certain extent, when the coating faces lateral shear stress, the coating surface is difficult to keep flat, resulting in limited anti-friction performance. On the other hand, after the most anti-friction surface layer of the coating is excessively worn, the exposed lower layer material may not have ideal friction performance, resulting in the gradual deterioration of the overall anti-friction performance of the coating as the service time increases. In particular, the layers are combined together by interfacial bonding force. When the coating is under high stress or high temperature conditions, the bonding force between the layers may be insufficient, resulting in peeling or cracking of the gradient anti-friction coating at the interface, resulting in the loss of anti-friction function.

[0004] Chinese patent application number 2020104185784 discloses a method for preparing a transversely soft and hard self-lubricating coating, which uses a method of pasting insulating materials to prepare a transversely alternating hard coating or soft coating on the surface of a substrate by electrospark deposition, thereby obtaining a self-lubricating coating with a transversely alternating soft and hard structure. However, the performance differences between adjacent coatings are large, resulting in large residual tensile stress in the coating and many surface defects in the coating. In addition, the insulating material has a short service life and is easily affected by the coating quality during pasting and removal. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a friction-reducing coating with a lateral gradient and a preparation method thereof. The friction-reducing coating with a lateral gradient has a gradient change along a direction parallel to the friction surface. The electrojet mask in-situ forming technology is used to achieve close integration of the strip textures with gradient composition changes during the forming process, forming a uniform and dense lateral gradient friction-reducing coating, which well ensures the quality and lubrication effect of the gradient friction-reducing coating.

[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0007] The first aspect of the present invention provides a friction-reducing coating with a lateral gradient, comprising self-lubricating material powder and metal powder combined into one body; the ratio of the self-lubricating material powder and the metal powder changes gradiently along a direction parallel to the friction surface;

[0008] The self-lubricating material powder is selected from one or more of MoS2 and WS2;

[0009] The metal powder is selected from one of Ti, Co or Ni;

[0010] The mass ratio of the self-lubricating material powder to the metal powder is (5-10):(0-5).

[0011] Optionally, the anti-friction coating with a lateral gradient includes 5 to 11 layers arranged in a direction parallel to the friction surface, with the proportion of self-lubricating material gradually increasing from the edge to the middle, and the mass ratio of self-lubricating material powder and metal powder in adjacent layers being a gradual gradient.

[0012] Optionally, the mass ratio of the self-lubricating material powder to the metal powder in the stratification at the edge position is smaller than that in the stratification at the center position; or the mass ratio of the self-lubricating material powder to the metal powder in the stratification at the edge position is greater than that in the stratification at the center position.

[0013] Optionally, the thickness of the anti-friction coating with a lateral gradient is 2 to 20 μm.

[0014] Optionally, the anti-friction coating with a lateral gradient is arranged on a high-temperature nickel-based alloy or YT15 cemented carbide substrate.

[0015] Optionally, each of the layers is distributed in strips, and the length direction of each layer is perpendicular to the direction of the friction force.

[0016] In a second aspect, a method for preparing a friction-reducing coating having a lateral gradient comprises the steps of:

[0017] S1. Mixing raw material powder, adhesive and solvent in a mass ratio of (5-15): (1-2): (8-10) to form a slurry, wherein the raw material powder includes self-lubricating material powder and metal powder;

[0018] S2. Using the electrojet method at a voltage of 2.0 to 3.5 kV, a slurry is used to obtain a layered wet film in a set area on the substrate; the slurry is replaced in other set areas to obtain multiple layers to form a friction-reducing coating wet film with a lateral gradient;

[0019] S3. The wet film of the gradient anti-friction coating is vacuum sintered at 1000-1500° C. for 60-120 min to obtain an anti-friction coating with a lateral gradient.

[0020] Optionally, in S1, the adhesive is selected from one of ethyl cellulose and polyvinyl alcohol.

[0021] Optionally, in S1, the solvent is selected from one of anhydrous ethanol and deionized water.

[0022] Optionally, in S1, the slurry meets the physical conditions for forming a cone jet: viscosity η<1.338Pa·s, conductivity K>10 -11 S / m, surface tension σ<50mN / m;

[0023] Optionally, in S1, the particle size of the raw material powder is 80 to 120 nm.

[0024] Optionally, in S2, a mask plate is used to limit the range of preparing the stratified wet film by the electrojet method.

[0025] Optionally, in the electrofluidization method of S2, the flow rate of the slurry is 15-20 μL / min, the inner diameter of the nozzle is 0.6-1.0 mm, the distance between the nozzle and the substrate is 1-5 mm, and the movement speed of the nozzle is 10-15 mm / s.

[0026] Optionally, in S2, the width of the single layered wet film is 0.1-1 mm.

[0027] Optionally, in S3, the vacuum degree of the vacuum sintering is 10 -3 ~10 -1 Pa.

[0028] The beneficial effects of the present invention are as follows:

[0029] 1. The friction-reducing coating with a transverse gradient provided by the present invention is structurally characterized by: a gradient change in composition and performance along a direction parallel to the friction surface, and after sintering, the components diffuse into each other in a gradual gradient, and the composition content between each layer transitions smoothly, maintaining good continuity, and the composition and performance exposed on the surface remain unchanged as the coating gradually becomes thinner. In the friction reduction process, since the material properties gradually change along the direction of the friction force, the stress is more evenly distributed on the coating surface. Compared with the traditional planar layered coating, the stress is no longer limited to the interface parallel to the friction surface, which can effectively reduce local stress concentration, better adapt to complex lateral loads, and better control the lateral diffusion of heat, thereby improving the lubrication performance and anti-peeling and anti-cracking performance of the coating, and extending the service life. It can be widely used in electronic devices, aerospace parts, automobiles, machine tool tools and other fields that require stable lubrication.

[0030] 2. The present invention uses the electrojet in-situ forming technology to form the slurry through the pores of the mask plate in a high-voltage electric field and then form it on the substrate after vacuum sintering. The prepared anti-friction coating with a lateral gradient has high density and few pores on the coating surface, which can well ensure the quality of the coating. It also has the characteristics of low friction coefficient, short production cycle and green environmental protection. It is easy to form a film on various flat substrates, uses less materials and has low cost, which is very suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0032] In order to show the positions of various parts, the distances or sizes between them are exaggerated in the figure, and the schematic diagram is for illustration only.

[0033] Figure 1 Schematic diagram of the structure of the anti-friction coating with lateral gradient in Example 1.

[0034] Figure 2 It is a schematic diagram of the preparation method of the anti-friction coating with a lateral gradient in Example 1.

[0035] Figure 3 It is a performance test result diagram of Example 1 and a traditional gradient anti-friction coating perpendicular to the friction surface.

[0036] Among them, 1. 50% MoS2-50% Ni stratification; 2. 60% MoS2-40% Ni stratification; 3. 70% MoS2-30% Ni stratification; 4. 80% MoS2-20% Ni stratification; 5. 90% MoS2-10% Ni stratification; 6. 100% MoS2-0 Ni stratification. DETAILED DESCRIPTION

[0037] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0038] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0039] Example 1

[0040] This embodiment provides a friction-reducing coating with a transverse gradient, which is arranged on the surface of the friction surface of the friction component, and the friction surface substrate of the friction component is a nickel-based high-temperature alloy. The friction-reducing coating with a transverse gradient includes self-lubricating material (MoS2) powder and metal (Ni) powder sintered into one. The friction-reducing coating with a transverse gradient includes 11 strip-shaped layers distributed side by side on the friction surface, such as Figure 1 As shown in the figure, in the order from both sides to the middle, there are 50% MoS2-50% Ni layer 1, 60% MoS2-40% Ni layer 2, 70% MoS2-30% Ni layer 3, 80% MoS2-20% Ni layer 4, 90% MoS2-10% Ni layer 5 and 100% MoS2-0 Ni layer 6. The width of each strip layer is about 1mm, and the ratio of MoS2 powder to Ni powder in each strip layer is 5:5, 6:4, 7:3, 8:2, 9:1, 10:0, 9:1, 8:2, 7:3, 6:4 and 5:5 respectively. That is: the content of MoS2 powder in the middle position is high; the content of MoS2 powder at both sides gradually decreases; at the edge position, the content of MoS2 powder drops to the lowest, and the ratio with Ni powder is 1:1. The thickness of the coating in the direction perpendicular to the friction surface is 12μm.

[0041] Preparation method Figure 2 As shown, the steps include:

[0042] S1. MoS2 powder with a particle size of 100 nm, Ni metal powder with a particle size of 100 nm, anhydrous ethanol (solvent) and ethyl cellulose (binder) are prepared in a mass ratio of 5:5:2:10, 6:4:2:10, 7:3:2:10, 8:2:2:10, 9:1:2:10 and 10:0:2:10, and then mixed evenly by a high-energy ball mill to obtain slurries of different proportions. The slurries can meet the physical conditions for forming a cone jet: viscosity η<1.338Pa·s, conductivity K>10 -11 S / m and surface tension σ<50mN / m.

[0043] S2. Prepare a mask plate made of 304 stainless steel with a size of 15×15×0.08 (length×width×thickness) mm 3 The aperture size on the mask plate is 14×1×0.08 (length×width×thickness) mm 3, ultrasonically clean the friction parts and the mask plate in anhydrous ethanol for 20 minutes to remove surface dirt; load the coating slurry of different proportions obtained in S1 into the electrojet in-situ forming equipment, form a stable jet in a high-voltage electric field of 2.6kV, and use the nozzle to pass the slurry through the pores of the mask plate to in-situ form on the substrate to obtain a single-row coating with the same pore size; after the single-row coating is prepared, replace the slurry, move the mask plate, and repeat the preparation of the single-row coating, so that multiple single-row coatings are spliced ​​into an overall coating wet film; during the preparation process, the flow rate of the slurry is 18μL / min, the inner diameter of the nozzle is 0.6mm, the distance between the nozzle and the substrate is 2mm, and the movement speed of the nozzle is 10mm / s.

[0044] S3, vacuum sinter the friction parts with the coating wet film, the vacuum sintering temperature is 1000℃, the vacuum degree is 10 -3 Pa, holding time 60min; during the process, anhydrous ethanol is evaporated, the products formed by the thermal decomposition of ethyl cellulose are discharged in the form of gas, the remaining MoS2 powder and Ni metal powder in the coating are gradually densified, the residual stress between the layers due to the different composition ratios is eliminated, and the coating is densified; a friction-reducing coating with a lateral gradient can be obtained.

[0045] In this embodiment, the proportion of metal material powder at the edge is higher than that at the center, resulting in high hardness of the coating at the edge, and low hardness but good lubricity of the coating near the center. During the service process, arc-shaped pits are formed to store the self-lubricating material. At the same time, due to the change in height difference, the actual contact area between the grinding pairs is reduced. At the same time, local stress concentration is effectively reduced, which can better adapt to complex lateral loads and better control the lateral diffusion of heat, thereby improving the lubrication performance and anti-peeling and anti-cracking performance of the coating and extending the service life.

[0046] Example 2

[0047] Compared with Example 1, the friction surface substrate of the friction component of this embodiment is YT15 cemented carbide, the self-lubricating material powder is selected as WS2 powder, and the metal powder is selected as Co powder; the anti-friction coating with a transverse gradient includes 11 strip layers distributed side by side on the friction surface, the width of each strip layer is about 0.8 mm, and the ratio of WS2 powder to Co powder in each strip layer is 5:5, 5:4, 5:3, 5:2, 5:1, 5:0, 5:1, 5:2, 5:3, 5:4 and 5:5 respectively. The thickness of the coating in the direction perpendicular to the friction surface is 20 μm.

[0048] The difference between the preparation method and Example 1 is that:

[0049] In S1, WS2 powder with a particle size of 100 nm, Co powder with a particle size of 100 nm, deionized water (solvent) and polyvinyl alcohol (binder) are configured in a mass ratio of 5:5:2:8, 5:4:2:8, 5:3:2:8, 5:2:2:8, 5:1:2:8 and 5:0:2:8, and their characteristics all meet the physical conditions for forming a cone jet: viscosity η<1.338 Pa·s, conductivity K>10 -11 S / m and surface tension σ<50mN / m.

[0050] In S2, the mask plate material is 45# steel, and the size of the mask plate is 16×16×0.1mm 3 , the surface pore size is 15×0.8×0.1mm 3 , electrojet in-situ forming was carried out in a high voltage electric field of 2.8 kV, the flow rate of the slurry was 15 μL / min, the inner diameter of the nozzle was 0.8 mm, the distance between the nozzle and the substrate was 3 mm, and the movement speed of the nozzle was 12 mm / s.

[0051] In S3, the vacuum sintering temperature is 1200°C and the vacuum degree is 10 -2 Pa, holding time 90min.

[0052] In this embodiment, the gradient trend of the self-lubricating material and the metal powder is: the mass ratio of the self-lubricating material powder and the metal powder at the edge is greater than that at the center, resulting in a low hardness coating at the edge but good lubricity, and a high hardness coating near the center. In the service process, the high hardness area in the middle has excellent wear resistance, can withstand most of the loads and stresses, and has a strong ability to resist deformation. The low hardness lubrication areas on both sides can absorb and relieve part of the stress through plastic deformation, while providing uninterrupted lubrication. The lubrication performance and anti-peeling and anti-cracking performance of the coating are improved, and the service life is extended. It is more suitable for anti-friction lubrication of groove structures.

[0053] Comparative Example 1

[0054] A friction component with a friction reduction coating, the friction reduction coating comprising self-lubricating material (MoS2) powder and metal (Ni) powder sintered into one. The friction reduction coating comprises a plurality of sublayers distributed parallel to the friction surface, and in order from the inside to the outside, the composition ratio of the sublayers is: a sublayer of 50% MoS2-50% Ni, a sublayer of 60% MoS2-40% Ni, a sublayer of 70% MoS2-30% Ni, a sublayer of 80% MoS2-20% Ni, a sublayer of 90% MoS2-10% Ni and a sublayer of 100% MoS2-0 Ni, the thickness of each sublayer is 2 μm, and the thickness of the entire friction reduction coating is 12 μm.

[0055] The equipment used in the preparation method is the same as that in Example 1, and the raw material requirements are the same as those in Example 1. After the slurry is prepared, the electrojet method is used to prepare the layer by layer, and then a vacuum sintering treatment is performed. The vacuum sintering temperature is 1000°C and the vacuum degree is 10 - 3 Pa, holding time 60min.

[0056] Test example

[0057] The test method includes: using a reciprocating friction and wear tester (UMT-2, American Tribology Center) to conduct dry friction and wear tests on the coating samples. The friction direction is perpendicular to each column of the transverse alternating coating to make full use of the transverse alternating coating; the test conditions are at 25°C, the load is 6N (accuracy 0.01N), the sliding speed is 6mm / s, the sliding time is 30min, the total sliding distance is 9000mm, and the amplitude is 11mm; the wear piece is a 304 stainless steel ball with a diameter of 9.525mm; each test is repeated three times to ensure accuracy.

[0058] The test objects are the friction component with the anti-friction coating having a transverse gradient in Example 1 and the friction component with the traditional MoS2 / Ni gradient anti-friction coating in Comparative Example 1.

[0059] Test results such as Figure 3 As shown in the figure, the dark line is the friction coefficient of Example 1, and the light line is the friction coefficient of Comparative Example 1. It can be seen that: the friction coefficient of Example 1 first increases and then decreases, and after reaching stability at around 600s, its friction coefficient is 0.095±0.015, and the friction coefficient of Comparative Example 1 continues to increase with the increase of friction time, and continues to increase after 600s, and is statistically 0.130±0.021; within the stable range of the friction coefficient of Example 1, the difference in friction coefficient between Example 1 and Comparative Example 1 is about 28.0%, indicating that the transverse gradient layer has a better lubrication effect.

[0060] In the technical solution of the present invention represented by Example 1, the anti-friction coating with a transverse MoS2 / Ni gradient has good lubrication performance provided by MoS2, and Ni provides strength and anti-friction performance. Through the gradual change of material composition in the horizontal direction, the transverse load is evenly dispersed to reduce stress concentration; the lateral diffusion of heat is improved, and the influence of local thermal stress and thermal fatigue is reduced. Compared with the vertical gradient layer, the anti-friction coating with a transverse gradient reduces the number of interfaces in the vertical direction and avoids failure caused by interlayer interface peeling or cracking; at the same time, the hardness difference of its transverse gradient structure reduces the actual contact area between the grinding pairs, improves the overall lubrication performance, and finally enables the coating to show good lubricity in high temperature, high load, and complex stress working environment.

[0061] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A friction-reducing coating with a lateral gradient, characterized in that: It comprises self-lubricating material powder and metal powder combined into one; the ratio of the self-lubricating material powder and the metal powder changes gradiently along the direction parallel to the friction surface; The self-lubricating material powder is selected from one or more of MoS2 and WS2; The metal powder is selected from one of Ti, Co or Ni; The mass ratio of the self-lubricating material powder to the metal powder is (5-10):(0-5).

2. The friction reducing coating with a lateral gradient according to claim 1, characterized in that: It comprises a plurality of layers arranged in a direction parallel to the friction surface, and the mass ratio of the self-lubricating material powder and the metal powder in adjacent layers is a gradual gradient.

3. The friction reducing coating with lateral gradient according to claim 2, characterized in that: The mass ratio of the self-lubricating material powder to the metal powder in the stratification at the edge position is smaller than that in the stratification at the center position; or the mass ratio of the self-lubricating material powder to the metal powder in the stratification at the edge position is larger than that in the stratification at the center position.

4. The friction reducing coating with a lateral gradient according to claim 1, characterized in that: The thickness of the transverse gradient anti-friction coating is 2-20 μm.

5. A method for preparing a friction-reducing coating with a lateral gradient as claimed in any one of claims 1 to 4, characterized in that: Includes steps: S1. Mixing raw material powder, adhesive and solvent in a mass ratio of (5-15): (1-2): (8-10) to form a slurry, wherein the raw material powder includes self-lubricating material powder and metal powder; S2, using an electrojet method at a voltage of 2.0 to 3.5 kV to obtain a layered wet film in a set area on the substrate using a slurry; Replace the slurry to obtain multiple layers in other set areas to form a friction-reducing coating wet film with a lateral gradient; S3. The wet film of the anti-friction coating with a lateral gradient is vacuum sintered at 1000-1500° C. for 60-120 min to obtain the anti-friction coating with a lateral gradient.

6. The method for preparing a friction reducing coating with a lateral gradient according to claim 5, characterized in that: In S1, the binder is selected from one of ethyl cellulose and polyvinyl alcohol; Optionally, in S1, the solvent is selected from one of anhydrous ethanol and deionized water.

7. The method for preparing a friction-reducing coating with a lateral gradient according to claim 5, characterized in that: In S1, the particle size of the raw material powder is 80 to 120 nm.

8. The method for preparing a friction reducing coating with a lateral gradient according to claim 5, characterized in that: In S2, a mask is used to limit the range of preparing the layered wet film by the electrojet method; Optionally, in the electrofluidization method of S2, the flow rate of the slurry is 15-20 μL / min, the inner diameter of the nozzle is 0.6-1.0 mm, the distance between the nozzle and the substrate is 1-5 mm, and the movement speed of the nozzle is 10-15 mm / s.

9. The method for preparing a friction-reducing coating with a lateral gradient according to claim 5, characterized in that: In S2, the width of the single layered wet film is 0.1-1 mm.

10. The method for preparing a friction reducing coating with a lateral gradient according to claim 5, characterized in that: In S3, the vacuum degree of the vacuum sintering is 10 -3 ~10 -1 Pa.

Citation Information

Patent Citations

  • Gliding Element

    CN102428208A

  • Multi-soft-coating nano texture tool based on electrohydrodynamic jet deposition and preparation method thereof

    CN107779858A

  • Preparation method of surface gradient thin film

    CN108179384A

  • Industrial fine copper surface nickel-based laser alloying layer and preparation method thereof

    CN108611635A

  • Two-dimension gradient structure transition layer

    CN109825796A